Subject Files
In this series the materials include press clippings, news agency releases, RFE/RL research papers and background analyses, transcripts of radio broadcasts, samizdat and émigré publications, and information items. The documents offer a broad insight into the postwar history of Hungary. They focus on issues of topical interest: domestic and foreign politics, security, opposition to the regime and exile, economy and trade, culture, environment. The most extensive files are on the communist party and other political parties, foreign relations, religion, and environmental protection - with special attention to the Bős-Nagymaros (Gabcikovo) dam constructions. There is an extremely rich coverage of the 1956 Revolution as well: one can find the transcripts of RFE programs during theevents, as well as documents on the debates of the Petőfi-Circle, political trials, victims and martyrs of 1956, commemorations, and Hungarian and Western reactions to the Revolution.